Analisis Ekonomi Pembuatan Ikan Asap Berbahan Bakar Arang dan Sabut Kelapa - Asmara, Sandi; Aldama, Daffa Chairunissa; Warji, Warji; Kuncoro, Sapto (abe.fp.unila.ac.id, 2024)
The main sector in Indonesia is fisheries, particularly in the industry and export of high-value seafood products. Indonesia's fisheries potential is significant and can serve as a funding source for development with proper management. Effective and efficient drum-type fish smoking machines are needed for post-harvest processing to improve the smoking process compared to traditional methods. Economic analysis is conducted to understand the performance of these smoking machines and provide beneficial information to the general public. This study aims to evaluate the performance of drum-type fish smoking machines to provide economic feasibility information to the public. Data collected are then analyzed to assess the performance and economic feasibility of the smoking machines. Based on the analysis, operating the drum-type fish smoking machine can produce 4 kg of smoked catfish using 2.6 kg of charcoal and 3.43 kg of coconut husks for each smoking session. Over 14 working days per month, Net Present Value (NPV) is Rp. 59.215.651/year, Benefit-Cost (B/C) ratio is 1,553. The sensitivity analysis shows no significant changes in the economic feasibility of the smoking machine with varying working days. Keywords: Break Even Point (BEP), B/C Ratio, Drum type of smoke fish, Internal Rate of Return (IRR). Net Present Value (NPV).